Effects of electric field stimulation timing on calcium dynamics of cultured cardiomyocytes. (30th September 2013) - Miyashita, Leo; Takayama, Yuzo; Haga, Tatsuya; Suzuki, Takafumi; Mabuchi, Kunihiko
Abstract: In this article, in order to propose the effective and low‐intensity stimulation method for cardiomyocyte, electric field stimulation was applied to cultured cardiomyocytes, and its responses were recorded and analyzed in term of applied timing by calcium imaging. As a result, we confirmed that electric field stimulation after peak of calcium transients (late‐phase stimulation) lengthened the full width at third maximum of calcium transient cycles temporarily. By optimizing the applied timing, electric field stimulation would be more effective method for controlling cardiomyocyte dynamics. © 2013 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.